Clinical Efficacy of Atorvastatin and PCSK9 Inhibitors in Patients With Borderline Coronary Lesions: An Intravascular Ultrasound Assessment - Zeyu Xu BM; Yi Fang MM; Yong Peng MM; Chunhua Zhang BM; Chunhua Zheng MD (Journal of Cardiovascular Pharmacology and Therapeutics)
Background While PCSK9 inhibition has proven safe and effective, there is limited research on using intravascular ultrasound (IVUS) to assess the impact of atorvastatin combined with PCSK9 inhibitors on borderline coronary lesions. Methods From June 2022 to June 2025, a detailed analysis of biochemical markers, coronary angiography (CAG), and IVUS was conducted on 69 patients with borderline coronary lesions after different treatments. Results Of the 69 patients enrolled, 60 completed the 48-week study. All groups showed significant low-density lipoprotein cholesterol (LDL-C) reductions, with Group C (Alirocumab + Atorvastatin) having the largest decrease from 3.64 to 1.48 ( P  < .001). At 48 weeks, arterial lumen volumes increased in all groups, but Group C's was significantly larger than Groups A (Alirocumab + placebo) and B (Atorvastatin + placebo) ( P  = .038). Group C also had a greater reduction in plaque volume compared to Groups A and B ( P  = .041). Conclusion Alirocumab and Atorvastatin together significantly lowered LDL-C levels and improved the vascular environment, notably reversing plaque in patients with borderline coronary lesions.